The Relationship Between Insomnia, Working Memory, and Inhibition Control with Academic Achievement: A Facial Analysis Study - Eugenia Dhea Adeline; Azam Syukur Rahmatullah; Halim Purnomo (MASI Mandiri Edukasi, 2026)
Sleep deprivation is one of the crucial factors that contribute to the decline in adolescent academic achievement, but objective measurements of this condition are still limited. This study aims to analyze the relationship between physiological insomnia symptoms, executive function (working memory and inhibitory control), and student academic achievement. The method used is a quantitative approach with a cross-sectional design, involving 200 students of Vocational High Schools (SMK) in North Kalimantan. Physiological insomnia symptoms were objectively measured using Computer-Based Facial Analysis via the Eye Aspect Ratio (EAR) and Mouth Aspect Ratio (MAR) indicators, while executive function was measured using the N-Back and Stroop tasks. Data were analyzed using Structural Equation Modeling (SEM) with 5,000 bootstrapping resamples. The results showed that physiological insomnia symptoms had a negative, significant effect on executive function (β = -0.45; p < 0.001), while executive function had a positive, significant effect on academic achievement (β = 0.56; p < 0.001). Mediation analysis showed that working memory and inhibitory control partially mediated the relationship between insomnia and academic achievement (indirect effect = -0.254). The conclusion of this study confirms that insomnia contributes to decreased academic achievement by degrading cognitive function. From the perspective of Islamic educational psychology, these findings reinforce the importance of maintaining sleep quality as part of efforts to maintain reason (hifz al-'aql), as well as encouraging the integration of sleep hygiene education in the school environment to improve students' cognitive readiness.